How Friedman and Schwartz became monetarists - James R. Lothian; George S. Tavlas (Duke University, Center for the History of Political Economy (CHOPE), 2016)
During the late-1940s and the early-1950s Milton Friedman favored a rule under which fiscal policy would be used to generate changes in the money supply with the aim of stabilizing output at full employment. He believed that the economy is inherently unstable because of endogenous movements in money supply under a fractional-reserve banking system. In her work, Anna Schwartz downplayed the role of monetary factors of business cycles and the role of monetary policy as a stabilization tool. We show how the joint work of Friedman and Schwartz from 1948 to 1958 led Friedman to view money as the "primary mover" in the business cycle and underpinned his shift to a rule based on money growth so that discretionary monetary policy would not act as a source of destabilizing shocks. The decisive factor in the evolution of Friedman's thinking was the empirical confirmation that the Great Depression had been both initiated and deepened by the Fed. The largely neglected influence of Clark Warburton on the evolution of Friedman's thinking provides a missing - but crucial - link in explaining Friedman's recognition of the role of monetary factors in the Great Depression and of the Fed's ability to offset the destabilizing effects produced by shifts from deposits into currency under a fractional-reserve banking system.
Keywords: B22; E52; 330; Milton Friedman; Anna Schwartz; Clark Warburton; monetary rules; quantity theory of money; fiscal policy; Great Depression